Analisis Ketersediaan Ruang Terbuka - Friski Dermawan Zebua; Ingat Selamat Ziliwu; Franklin Dela Famatohu Zega; Ikhtiar Aronifati Daeli (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the availability of open space in Gunungsitoli City in terms of area, distribution, and its compliance with applicable standards. The research employs a descriptive quantitative approach using primary data obtained through field observations and secondary data from relevant institutions. The analysis is conducted using a spatial approach based on Geographic Information Systems (GIS) as well as calculations of the ratio of open space to population. The results indicate that the availability of open space in Gunungsitoli City has not yet met the minimum standard of 30% of the total area as regulated by national policy. In addition, the distribution of open space tends to be uneven and concentrated in the city center. In terms of quality, some open spaces are not optimally managed, resulting in low utilization by the community. These limitations affect ecological functions, such as temperature control and air quality improvement, as well as social functions as spaces for community interaction. Therefore, more integrated planning and management efforts are needed to improve the availability and quality of open space in Gunungsitoli City as part of sustainable urban development.